2020
DOI: 10.1186/s13028-020-00529-z
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of acute outbreaks of respiratory disease in Norwegian fattening pig herds

Abstract: Background: Respiratory diseases are major health concerns in the pig production sector worldwide, contributing adversely to morbidity and mortality. Over the past years there was a rise in reported incidents of respiratory disease in pigs in Norway, despite population wide freedom from Aujeszky´s disease, porcine reproductive and respiratory syndrome, porcine respiratory corona virus and enzootic pneumonia. The main objective of this study was to investigate acute outbreaks of respiratory disease in conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The population is structured in a hierarchical pyramid, with genetic nucleus and multiplier herds comprising the two apex tiers and unidirectional live animal trade downwards to commercial herds with sows and specialized finishing herds. The national pig health status is favourable, as the population is free from several important (viral and bacterial) pathogens that are commonly occurring in many pig populations worldwide [ 10 , 11 ]. However, one of the major respiratory disease causing pathogens in Norway is Actinobacillus pleuropneumoniae (APP) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The population is structured in a hierarchical pyramid, with genetic nucleus and multiplier herds comprising the two apex tiers and unidirectional live animal trade downwards to commercial herds with sows and specialized finishing herds. The national pig health status is favourable, as the population is free from several important (viral and bacterial) pathogens that are commonly occurring in many pig populations worldwide [ 10 , 11 ]. However, one of the major respiratory disease causing pathogens in Norway is Actinobacillus pleuropneumoniae (APP) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The national pig health status is favourable, as the population is free from several important (viral and bacterial) pathogens that are commonly occurring in many pig populations worldwide [ 10 , 11 ]. However, one of the major respiratory disease causing pathogens in Norway is Actinobacillus pleuropneumoniae (APP) [ 10 ]. With the exception of specific pathogen-free (SPF) herds that are clinically and serologically negative for APP, this agent is widely prevalent and disease caused by APP is common [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These isolates mainly stemmed from cases of clinical pleuropneumonia; however, a minority of isolates (n = 2) were cultured by swabbing from pneumonic lungs at slaughter with no prior remarks of clinical signs. Serovar determination was performed by the method as previously described (Cohen et al, 2020). Non-APP8 isolates (n = 5), collected at the NVI in the same period, were excluded from the study.…”
Section: The Norwegian Isolate Repositorymentioning
confidence: 99%
“…Among the 19 described serovars of A. pleuropneumoniae (Stringer et al, 2021), serovar 8 (APP8) is most commonly isolated from cases of acute porcine pleuropneumonia in Norway (Cohen et al, 2020;Norwegian Veterinary Institute, 2021b) and the UK (O'Neill et al, 2010;Li et al, 2016). In Denmark, APP8 has also been isolated from clinical cases, although earlier studies have shown it is not the most prevalent serovar (Møller et al, 1992;Kokotovic and Angen, 2007).…”
Section: Introductionmentioning
confidence: 99%